Baroreflex dysfunction is more severe in patients with a history of moderate or severe TBI than in patients after mild TBI - Hilz, Max-Josef; Roy, Sankanika; Wang, R.; Ammon, Fabian; Hoesl, K.; Markus, Jörg; Muresanu, D. (EUROPEAN JOURNAL OF NEUROLOGY, 2019)
CRIS-Team WoS Importer:2019-07-30

CT-derived left ventricular global strain: a head-to-head comparison with speckle tracking echocardiography - Ammon, Fabian; Bittner, D.; Hell, M.; Mansour, H.; Achenbach, Stephan; Marwan, Mohamed; Arnold, Martin (International Journal of Cardiovascular Imaging, 2019)
We assessed CT-derived left ventricular strain in a cohort of patients referred for transcatheter aortic valve implantation (TAVI) and validated it against 2 dimensional speckle tracking echocardiography as the gold standard. 65 consecutive patients with symptomatic aortic valve stenosis referred for CT imaging prior to TAVI were included in this analysis. For all patients, retrospectively ECG-gated multi-phase functional CT data sets acquired with identical reconstruction parameters were available. All data sets were acquired using a third generation dual source system. In all patients, multiphase reconstructions in increments of 10% of the cardiac cycle were rendered (slice thickness 0.75, increment 0.5 mm, medium smooth reconstruction kernel) and transferred to a dedicated workstation (Ziostation2, Ziosoft Inc., Tokyo, Japan). Additional functional reconstructions for dynamic assessment and quantification of strain were processed. Multiplanar reconstructions (MPR) of the left ventricle similar to standard echocardiographic 4, 2 and apical 3 chamber views were rendered in CT. Similar to echocardiographic longitudinal strain, the perimeter of the left ventricle was manually traced within the myocardium and peak maximal shortening as a parameter representing longitudinal strain was calculated for each view and averaged to obtain a marker for global longitudinal strain (CT perimeter-derived strain). Furthermore, for quantification of 3-dimensional strain, endocardial and epicardial borders of myocardium were marked in six short axis views and peak maximum 3- dimensional strain of the myocardium was calculated in standard six basal, six mid and four apical segments. 3-dimensional strain values of the 16 standard segments as well as perimeter-derived strain values in the three standard windows were averaged to obtain global strain. Echocardiography was performed in all patients before CT data acquisition. Digital loops were acquired from three apical views (four-, two-, and three chamber views). For assessment of 2 dimensional global longitudinal strain (GLS), recordings were processed with acoustic-tracking software allowing offline semiautomated speckle-based strain analyses. The mean age of all 65 patients was 81 ± 5 years. The mean echocardiographic ejection fraction and mean echocardiographic GLS were 50 ± 12% and −13.6 ± 4.5%, respectively. The mean CT-derived peak 3-dimensional global strain and mean peak strain derived by perimeter was 43.2 ± 13.5% and −11.2 ± 3.5%, respectively. Both CTderived global 3D-strain and perimeter derived strain showed a significant correlation to GLS derived by echocardiography (r = −0.8, p < 0.0001 for 3D strain and r = 0.71, p < 0.0001 for perimeter-derived strain). Bland-Altman analysis showed a systematic underestimation (i. e. worse strain values) of CT perimeter-derived strain compared to GLS by echocardiography (mean difference −2.4% with 95% limits of agreement between 4% to −9%). ROC Curve analysis assuming a normal GLS when less than −18% showed that a CT-derived peak 3-dimensional global strain cut-off-value of 45% has a sensitivity of 91% and a specificity of 60% for detecting normal left ventricular strain (AUC 0.81, p = 0.001). For CT perimeter-derived strain, a cut-off value of −12%—assuming a normal echocardiographic GLS when less than −18%—achieved a sensitivity of 82% and a specificity of 61% (AUC of 0.82, p = 0.001) for detecting abnormal left ventricular strain. Using dedicated software, assessment of CT-derived left ventricular strain is feasible and comparable to strain derived by echocardiographic 2 dimensional speckle tracking.
CRIS-Team Scopus Importer:2019-05-07
Keywords: Cardiac CT angiography; Echocardiography; Left ventricular global strain; Speckle tracking

CT-derived left ventricular global strain in aortic stenosis patients referred for transcatheter aortic valve implantation: a head-to-head comparison with echocardiography - Ammon, Fabian; Bittner, D.; Hell, M.; Schuhbaeck, A.; Röther, Jens; Feyrer, R.; Achenbach, Stephan; Marwan, Mohamed; Arnold, Martin (EUROPEAN HEART JOURNAL, 2018)
CRIS-Team WoS Importer:2019-03-15

CT-derived left ventricular global strain in aortic valve stenosis patients: A comparative analysis pre and post transcatheter aortic valve implantation - Ammon, Fabian; Bittner, D.; Röther, Jens; Mekkhala, N.; Hell, M.; Schuhbaeck, A.; Gitsioudis, Gitsios; Feyrer, R.; Schlundt, Christian; Achenbach, Stephan; Marwan, Mohamed; Arnold, Martin (Journal of Cardiovascular Computed Tomography, 2018)
INTRODUCTION: We assessed the potential of CT strain to detect changes in myocardial function in patients referred for TAVI pre and post intervention. PATIENTS AND METHODS: 25 consecutive patients with symptomatic aortic valve stenosis in whom TAVI had been performed were included in this analysis. Functional CT data sets acquired before and 3 to 6 months after TAVI were available. Multiphase reconstructions in increments of 10% of the cardiac cycle were rendered and transferred to a dedicated workstation (Ziostation2, Ziosoft Inc., Tokyo, Japan). For quantification of left ventricular strain, multiplanar reconstructions of the left ventricle in standard 4 chamber, 2 chamber as well as apical 3 chamber views were rendered. The perimeter of the left ventricle was traced dynamically through the cardiac cycle. Peak strain was calculated for each patient pre and post intervention. Furthermore, for quantification of 3-dimensional maximum principal strain, 2 volumetric regions of interests (VOI) were placed per each basal, mid and apical segment of the previously mentioned MPRs and peak maximal principal strain was calculated. Maximum principal strain as well as perimeter-derived longitudinal strain values in the three standard windows were averaged to obtain global strain. RESULTS: 25 patients were included in this analysis (mean age 78 ± 9 years, 13 males). Peak global maximum principal strain was significantly higher at follow-up compared to baseline (0.46 ± 0.19 vs. 0.59 ± 0.18, respectively, p = 0.001). Similarly global longitudinal strain derived by perimeter was significantly lower - implying better contraction - compared to baseline (-8.6% ± 2.8% vs. -9.8% ± 2.6%, respectively, p = 0.006). CONCLUSION: Using dedicated software, assessment of CT derived left ventricular strain is feasible. In patients treated with transcatheter aortic valve replacement, CT-derived parameters of global myocardial strain improve onshort-term follow-up.
EVALuna2:35994

Eyeball pressure stimulation induces subtle sympathetic activation in patients with a history of moderate or severe traumatic brain injury - Wang, Ruihao; Hoesl, Katharina M.; Ammon, Fabian; Markus, Jörg; Koehn, Julia; Roy, Sankanika; Liu, Mao; de Rojas Leal, Carmen; Muresanu, Dafin; Flanagan, Steven R.; Hilz, Max-Josef (Clinical Neurophysiology, 2018)
OBJECTIVE: After traumatic brain injury (TBI), there may be persistent central-autonomic-network (CAN) dysfunction causing cardiovascular-autonomic dysregulation. Eyeball-pressure-stimulation (EPS) normally induces cardiovagal activation. In patients with a history of moderate or severe TBI (post-moderate-severe-TBI), we determined whether EPS unveils cardiovascular-autonomic dysregulation. METHODS: In 51 post-moderate-severe-TBI patients (32.7 ± 10.5 years old, 43.1 ± 33.4 months post-injury), and 30 controls (29.1 ± 9.8 years), we recorded respiration, RR-intervals (RRI), systolic and diastolic blood-pressure (BPsys, BPdia), before and during EPS (120 sec; 30 mmHg), using an ocular-pressure-device (Okulopressor®). We calculated spectral-powers of mainly sympathetic low (LF: 0.04-0.15 Hz) and parasympathetic high (HF: 0.15-0.5 Hz) frequency RRI-fluctuations, sympathetically mediated LF-powers of BPsys, and calculated normalized (nu) LF- and HF-powers of RRI. We compared parameters between groups before and during EPS by repeated-measurement-analysis-of-variance with post-hoc analysis (significance: p < 0.05). RESULTS: At rest, sympathetically mediated LF-BPsys-powers were significantly lower in the patients than the controls. During EPS, only controls significantly increased RRIs and parasympathetically mediated HFnu-RRI-powers, but decreased LF-RRI-powers, LFnu-RRI-powers, and LF-BPsys-powers; in contrast, the patients slightly though significantly increased BPsys upon EPS, without changing any other parameter. CONCLUSIONS: In post-moderate-severe-TBI patients, autonomic BP-modulation was already compromised at rest. During EPS, our patients failed to activate cardiovagal modulation but slightly increased BPsys, indicating persistent CAN dysregulation. SIGNIFICANCE: Our findings unveil persistence of subtle cardiovascular-autonomic dysregulation even years after TBI.
EVALuna2:36357

Influence of image reconstruction parameters on diagnostic performance of on-site CT-derived FFR: Comparison with invasively measured FFR - Ammon, Fabian; Röther, Jens; Hell, M.; Schuhbaeck, A.; Achenbach, Stephan; Schlundt, Christian; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2018)
CRIS-Team WoS Importer:2019-03-15

Severity of traumatic brain injury correlates with long-term cardiovascular autonomic dysfunction - Hilz, Max J.; Wang, Ruihao; Markus, Jörg; Ammon, Fabian; Hoesl, Katharina M.; Flanagan, Steven R.; Winder, Klemens; Koehn, Julia (Journal of Neurology, 2017)
After traumatic brain injury (TBI), central autonomic dysfunction might contribute to long-term increased mortality rates. Central autonomic dysfunction might depend on initial trauma severity. This study was performed to evaluate differences in autonomic modulation at rest and upon standing between patients with a history of mild TBI (post-mild-TBI patients), moderate or severe TBI (post-moderate-severe-TBI patients), and healthy controls. In 20 post-mild-TBI patients (6-78 months after TBI), age-matched 20 post-moderate-severe-TBI patients (6-94 months after TBI) and 20 controls, we monitored respiration, RR intervals (RRI) and systolic blood pressure (BPsys) at supine rest and upon standing. We determined mainly sympathetic low (LF) and parasympathetic high (HF) frequency powers of RRI fluctuations, sympathetically mediated LF-BPsys powers, LF/HF-RRI ratios, normalized (nu) LF-RRI and HF-RRI powers, and compared data between groups, at rest and upon standing (ANOVA with post hoc testing). We correlated autonomic parameters with initial Glasgow Coma Scale (GCS) scores (Spearman test; significance: p < 0.05). Supine BPsys and LFnu-RRI powers were higher while HFnu-RRI powers were lower in post-moderate-severe-TBI patients than post-mild-TBI patients and controls. LFnu-RRI powers were higher and HFnu-RRI powers were lower in post-mild-TBI patients than controls. Upon standing, only post-mild-TBI patients and controls increased LF-BPsys powers and BPsys and decreased HF-RRI powers. GCS scores correlated positively with LFnu-RRI powers, LF/HF-RRI ratios, and inversely with HFnu-RRI powers, at standing position. More than 6 months after TBI, there is autonomic dysfunction at rest and upon standing which is more pronounced after moderate-severe than mild TBI and in part correlates with initial trauma severity.
EVALuna2:22558

Valsalva maneuver unveils central baroreflex dysfunction with altered blood pressure control in persons with a history of mild traumatic brain injury - Hilz, Max-Josef; Liu, Mao; Koehn, Julia; Wang, Ruihao; Ammon, Fabian; Flanagan, Steven R.; Hoesl, Katharina M. (BMC Neurology, 2016)
Patients with a history of mild TBI (post-mTBI-patients) have an unexplained increase in long-term mortality which might be related to central autonomic dysregulation (CAD). We investigated whether standardized baroreflex-loading, induced by a Valsalva maneuver (VM), unveils CAD in otherwise healthy post-mTBI-patients.In 29 healthy persons (31.3 ± 12.2 years; 9 women) and 25 post-mTBI-patients (35.0 ± 13.2 years, 7 women, 4-98 months post-injury), we monitored respiration (RESP), RR-intervals (RRI) and systolic blood pressure (BP) at rest and during three VMs. At rest, we calculated parameters of total autonomic modulation [RRI-coefficient-of-variation (CV), RRI-standard-deviation (RRI-SD), RRI-total-powers], of sympathetic [RRI-low-frequency-powers (LF), BP-LF-powers] and parasympathetic modulation [square-root-of-mean-squared-differences-of-successive-RRIs (RMSSD), RRI-high-frequency-powers (HF)], the index of sympatho-vagal balance (RRI LF/HF-ratios), and baroreflex sensitivity (BRS). We calculated Valsalva-ratios (VR) and times from lowest to highest RRIs after strain (VR-time) as indices of parasympathetic activation, intervals from highest systolic BP-values after strain-release to the time when systolic BP had fallen by 90 % of the differences between peak-phase-IV-BP and baseline-BP (90 %-BP-normalization-times), and velocities of BP-normalization (90 %-BP-normalization-velocities) as indices of sympathetic withdrawal. We compared patient- and control-parameters before and during VM (Mann-Whitney-U-tests or t-tests; significance: P < 0.05).At rest, RRI-CVs, RRI-SDs, RRI-total-powers, RRI-LF-powers, BP-LF-powers, RRI-RMSSDs, RRI-HF-powers, and BRS were lower in patients than controls. During VMs, 90 %-BP-normalization-times were longer, and 90 %-BP-normalization-velocities were lower in patients than controls (P < 0.05).Reduced autonomic modulation at rest and delayed BP-decrease after VM-induced baroreflex-loading indicate subtle CAD with altered baroreflex adjustment to challenge. More severe autonomic challenge might trigger more prominent cardiovascular dysregulation and thus contribute to increased mortality risk in post-mTBI-patients.
EVALuna2:22445